Medroxy-Progesterone acetate in AUB-O: is the intramuscular route better suited for low and middle income countries? An open-labelled randomised controlled trial - Sufia Shadab; Shipra Kunwar; Amrita Singh; Suman Nishad; Ayesha Ahmad (Al Ameen Medical College, 2024)
Objective: Our purpose was to evaluate the efficacy of oral medroxy progesterone acetate and intramuscular depot medroxy progesterone acetate in patients presenting with heavy menstrual bleeding in terms of reduction in the amount of blood loss, side effect profile and compliance. Study design: 50 patients with heavy menstrual bleeding were randomized into two groups, patients in group 1 (25 Patients) were given i/m depot medroxyprogesterone acetate on day 3 of menses after recruitment (total dosage 2) and Group 2 (25 patients) were given oral medroxyprogesterone acetate 10mg from day 3 of menses 8 hourly for 7 days followed by 12 hourly for 14 days cyclically for 6 months (total 294 dosages). Patients were assessed on two monthly intervals for next 6 months on the basis of change in haemoglobin levels and menstrual blood loss on the basis of PBAC score and side effects, if any. Results: No significant difference was found in the efficacy and side effect profile of i/m depot medroxyprogesteroneacetate and oral medroxyprogesteroneacetate in treatment of heavy menstrual bleeding. Conclusion: The findings of present study showed that both DMPA and oral MPA could be offered as an alternative owing to no difference in their clinical efficacy, however DMPA has better compliance and overall cost benefit as compared to oral MPA.